A1.43 Autologous tolerogenic dendritic cells in rheumatoid and inflammatory arthritis. (31st January 2014) - Bell, G; Anderson, A; Harry, R; Diboll, J; McColl, E; Dickinson, A; Hilkens, C; Isaacs, J D
Abstract : Background and Objectives: Current therapies used in the treatment of rheumatoid and inflammatory arthritis, although efficacious in treating symptoms, may non-specifically suppress the immune system with consequences such as increased risk of infection and malignancy. It is therefore desirable to develop more specific immune-modulatory therapies in order to specifically switch off the pathological immune response, inducing immune tolerance in an auto-antigen specific manner. Autologous tolerogenic dendritic cells are one such therapy, with promising results already noted in animal models of arthritis. We are performing an experimental phase Ia study of intra-articular tolerogenic dendritic cells in rheumatoid and inflammatory arthritis patients. Our primary and secondary objectives are to assess safety, tolerability and feasibility of treatment; exploratory objectives seek preliminary evidence of a beneficial therapeutic effect. Methods: An experimental medicine phase Ia study is underway. Peripheral blood mononuclear cells are isolated via leukapheresis and transferred to a GMP Facility for 7days. CD11 + monocytes are isolated using a Clinimacs ® and differentiated to tolDC using a combination of Il-4, GM-CSF, vitamin D3 and dexamethasone. On day 7 the product is released and administered arthroscopically into the target knee joint, allowing concurrent synovial biopsy. There are 3 dosing cohorts of 1, 3 and 10 million tolDC with a control arm (arthroscopic washout only), in a 3:1 ratio. Dose escalation criteria have been defined and a Data Monitoring and Ethics Committee established. Subjects are closely observed until 5 days post tolDC administration for a treatment-induced flare in the target joint. At day 14 repeat arthroscopy enables examination of the target joint and repeat synovial biopsies. Escape treatment in the form of intra-articular steroid may be administered at any time for a knee flare or persistent disease activity. Patients are followed until day + 90. Results: To date 10 subjects have been enrolled in study. Three subjects each have been treated with 1 and three million tolDC. A further subject has been treated with 10 million tolDC. Two patients have received placebo and in one further subject tolDC failed quality control. Overall patient acceptability has been high. All subjects have required intra-articular steroid at day 14 for persistent knee disease activity, apart from the subject in the high dose (10million tolDC) cohort. Two serious adverse events have been documented (pneumonia and systemic RA flare), in a patient who received one million tolDC. Conclusion: In this ascending dose phase I study of intra-articular tolDC we have not seen evidence of acute toxicity. Our results to date suggest that the intra-articular administration of tolDC is safe (does not induce an acute flare of inflammatory arthritis) and is acceptable to patients.